Antibacterial, antifungal and antioxidant activities of whole plant chemical constituents of Rumex abyssinicus - Irene Chinda Kengne; Léonel Donald Tsamo Feugap; Abdel Jélil Njouendou; Claudia Darille Jouogo Ngnokam; Mahamat Djamalladine Djamalladine; David Ngnokam; Laurence Voutquenne-Nazabadioko; Jean- (BMC, 2021)
Abstract Background Antibiotic resistance has contributed to the burden of infectious diseases both in the hospital and community setting, and represents a great threat to public health. Previous studies have revealed the role of reactive oxygen species as intermediate mediators of tissue damage, following antibiotherapies, indicating the need of associating antioxidants to these treatments. Therefore, the present work was designed to study the antibacterial, antifungal and antioxidant activities of extracts and compounds from Rumex abyssinicus Jacq. (Polygonaceae), as well as to investigate the antibacterial mechanisms of action of the most effective agents. Methods The plant extracts were prepared by maceration in organic solvents followed by column chromatography of the EtOAc fraction and purification of different fractions which led to the isolation and characterization of pure compounds. The antimicrobial activities of the extracts/compounds and their combinations with ciprofloxacin and fluconazole were evaluated using the broth microdilution method by determining the minimum inhibitory concentration (MIC) and minimum microbicidal concentration (MMC). The effects of the extracts on the bacterial cell membrane and microbial respiratory chain dehydrogenase enzyme activity were determined by spectrophotometric methods. Antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and gallic acid equivalent antioxidant capacity (GAEAC) assays. Results Chrysophanol (1), physcion (2), Ergosta-6,22-diene-3,5,8-triol (3), emodin (4), 6-hydroxyemodin (citreorosein) (5), chrysophanein (6) and physcionin (7) were isolated from EtOAc fraction of R. abyssinicus and displayed different degrees of antimicrobial activities (MIC = 8-256 μg/mL). The MeOH extract and compounds 2 and 4 exhibited synergistic effects with ciprofloxacin and fluconazole. Compounds 1, 2 and the combined mixture of 6 + 7 displayed the highest antioxidant activity (GAEAC = 83.38-106.03 μg/mL). Conclusion R. abyssinicus is a potential source of antibacterial, antifungal and antioxidant agents. The antibacterial mechanisms of action of the MeOH extract and compound 2 are due to disruption of the cytoplasmic membrane and inhibition of the microbial respiratory chain dehydrogenase enzyme activity. To the best of our knowledge, this is the first report of test samples and ciprofloxacin / fluconazole association against MDR strains. The observed activity of the isolated compounds against bacteria and fungi including MDR strains deserves further exploration.